New Yuomys rodents from southeastern Qinghai-Tibet Plateau indicate low elevation during the Middle Eocene - Ni, Xijun; Li, Qiang; Deng, Tao; Zhang, Limin; Gong, Hao; Qin, Chao; Shi, Jingsong; Shi, Fuqiao; Fu, Shubing (Frontiers in Earth Science, 2023)
Yuomys are medium-body-sized Hystricomorpha rodents. They were mainly known from the Middle and Late Eocene of low elevation areas in China. Two new Yuomys were discovered from a locality near the Xueshuo Village of Litang County, Sichuan Province. The locality lies in the Gemusi pull-apart basin formed in the Litang Fault System (LTFS) in the Hengduan Mountains. The current average elevation is about 4200 meters. One of the two new Yuomys is larger and shows clear lophodont and unilateral hypsodont morphology, similar to Yuomys yunnanensis, which was discovered from the early Middle Eocene (Irdinmanhan, Asian Land Mammal Ages) in the Chake basin of Jianshui County, Yunnan Province. The Chake basin is one of the small pull-apart basins formed in the Xianshuihe-Xiaojiang Fault system (XSH-XJF). The other new Yuomys rodent is smaller, brachydont and less lophodont than the larger new species. The small new Yuomys is smaller than all known Yuomys except Yuomys huheboerhensis, which is from the early Middle Eocene Irdinmanhan of Inner Mongolia in Northern China. Given their narrow biochronological distribution and potential presumably preferred living environment, the occurrence of Yuomys in the pull-apart basins in LTFS and XSH-XJF suggests that the two deep fault systems probably started strike-slip movement by the early Middle Eocene about 49-45 million years ago. The well-studied Middle Eocene mammalian faunas from Henan and Inner Mongolia include Yuomys, primates and other low elevation forest mammals. We suggest that the two new Yuomys species reported here probably also lived in similar low elevation forest environment.